Designing of Environmental Physics Course Instruments about Ocean Wave Energy to Enhance Students' Creative Thinking Skills - Satriawan, Muhammad; Liliasari, Liliasari; Setiawan, Wawan; Abdullah, Ade Gafar (Universitas Negeri Surabaya, 2021)
Various factors become obstacles to developing renewable energy technology, including people's low knowledge of renewable energy and low 21st-century skills. Therefore, designing learning that can increase understanding of renewable energy and improve 21st-century skills simultaneously is essential. This study aimed to create programs of environmental physics lectures about OWC as a renewable energy source. This research was developmental research with analysis, design, and development stages. The products in this study were test instruments to measure creative thinking skills, OWC converters prototype, and a project-based lecture program oriented towards providing creative thinking skills through a combination of lectures in the classroom, laboratory, and marine environment. Five experts validated all products. In addition, besides experts' validation, the creative thinking test instrument was tested on 17 students who had taken environmental physics lectures. In contrast, a marine engineering laboratory tested the prototype at a university in Bandung. Experts' validity data were analyzed using the content validity ratio, while the test instrument data were calculated for reliability, validity, discrimination, and difficulty levels. Based on the results of expert validation, all products are feasible to be implemented. Based on the test results, the prototype developed functions well, while for the test instrument of 10 questions developed, only eight questions were eligible to be used. All of the products produced can be used as a reference and reference for lecturers or teachers who develop learning about renewable energy and equip students with creative thinking skills.